2022
DOI: 10.53730/ijhs.v6ns4.12001
|View full text |Cite
|
Sign up to set email alerts
|

outer membrane protein D gene mutations and carbapenem resistance in Pseudomonas Aeruginosa isolated from burns infection in Al-Najaf/Iraq

Abstract: The Most common mechanism used by P. aeruginosa for carbapenem resistance is the decrease of OM permeability, via accumulating mutations cause loss/reduce in the OprD gene expression. This study was designed to detect and determine the OprD gene mutations in carbapenem-resistant isolates of clinical P. aeruginosa isolated from burn wound infections. A 12/20 isolates were sequenced by Sanger method and the results were compared with wildtype (POA1) OprD gene sequence. The PCR products of 12/20 isolates were lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…Jaafar et al (2014), found that imipenem resistance was 24.4%. Al-Shara (2013) in Najaf reported less resistance against imipenem to be 7.4%. A recent study by Al-khudhairy and Al-Shammari (2020) in Iraq stated that imipenem resistance rate was 12.4%.…”
Section: Discussionmentioning
confidence: 96%
“…Jaafar et al (2014), found that imipenem resistance was 24.4%. Al-Shara (2013) in Najaf reported less resistance against imipenem to be 7.4%. A recent study by Al-khudhairy and Al-Shammari (2020) in Iraq stated that imipenem resistance rate was 12.4%.…”
Section: Discussionmentioning
confidence: 96%